Mechanics of reproductive differentiation in the land plants: a paradigm shift? - Lintilhac, Philip M. (Frontiers in Plant Science, 2024)
This article addresses the physical mechanics of gametogenesis in vascular plants. The earliest events that initiate reproductive differentiation in the land plants remain a mystery. How are the few cells that initiate reproductive differentiation specified and how is that information translated into action at the cellular level? In this article I propose a physical mechanism that resolves the problem of spatial targeting without invoking dependence on diffusible morphogens or other external signals. I suggest that the initiation of archesporial differentiation can instead be attributed to the confluence of organ geometry, surficial topography, and the physical mechanics of sporangial growth, resulting in the spontaneous emergence of an isotropic singularity that locates and precipitates archesporial differentiation. In discussing the logic of single-cell target selection and the limits of stochastic molecular signaling I propose that the sporangium would be better understood as a pressurized stress-mechanical lens that focuses turgor-generated growth forces on a central location, generating a physical singularity that locates and specifies the cell or cells that become the archesporium and initiates their transition from somatic proliferation to reproductive differentiation.